Pretoria Student Law Review 2020-14-2 (Pretoria University Law Press (PULP), 2020)
About the publication Honoured to present to you, the reader, the 2020 edition of the Pretoria Student Law Review (PSLR), an annual publication which is the pride of the best law faculty in Africa (according to the Times Higher Education World University Rankings). The University of Pretoria's Law Faculty ranks in the top 100 law faculties in the world, a feat unequalled in Africa. The PSLR is a student driven law review that creates an interactive forum for students, academics and legal professionals to discuss topical legal matters that challenge the status quo. At the beginning of this year, lay the fantasy of newness - presenting an opportunity to do great things. But as I reflect on the journey leading to this publication, I understand that the 2020 edition of the PSLR had an engine that ran on hope; faith; dedication; perseverance; commitment and hard work. Our predecessors had a vision to create a boldly outlined legacy for the PSLR, they spearheaded the setting up of a system that would last the lifespan of the PSLR. Today, some 13 years after the first edition of the PSLR, South Africa, the continent and the world at large are on the cusp of a new era - socially, economically and politically. When my journey as Editor-in-Chief commenced, I imagined the PSLR as a ship, whose captain was myself. Customarily, it is easy to be a captain of a ship in calm seas, but unlike most of my predecessors, I have had to be the captain of a ship through the heftiest of storms. The world was not truly prepared to face challenges presented by the Covid-19, let alone the PSLR. In the wake of the 4IR and this new age of technology, sailing this ship to success was still a heavy task to complete. It is therefore with great honour to have been able to successfully complete the task for which we, the 14th cohort of the Editorial Board, were called for. We have upheld the esteemed reputations that have been left by our predecessors. Fittingly, I wish to applaud my team for their inspiring commitment, outstanding contribution and service in maintaining the elevated standard of the PSLR. For indeed it is a publication, par excellence. Amidst the storms, we have spearheaded the establishment of a 'free-floating' PSLR Collection in the OR Tambo Law Library. This collection is dedicated to house all published PSLR editions, dating since the inception of the PSLR in 2007. We have established and strengthened relations with other Law Faculties in the country, and even beyond. We published the very first special edition of the PSLR, a focused edition that covers a critical issue brought before the South African Law Deans Association - the Decolonisation of Legal Education. We have established a system by which all authors who publish with us, ought to have an ORCID iD. We have adopted internal regulations that outline the principles that govern the Editorial Board. We have spearheaded the adoption and implementation of a policy that forces us to comply with DHET Standards in order to be a DHET Accredited Journal so as to encourage and foster a student culture of critical research & writing in legal academia. I am truly proud of the work that the authors have put into their articles and I would like to thank them for their submissions and tireless efforts to produce quality articles. More-so, I am proud of the Editorial Board for being able to work under immense pressure. This edition would have not been possible without the dedication and hard work of this dream team. I remain indebted to you all: Adelaide Chagopa, Kayla Thomas, Marcia van der Merwe, Nicholas Herd and Phenyo Sekati. It has been a great pleasure and a privilege to have worked with you on this annual edition. A note of thanks to Dr Gustav Muller in his capacity as the Guardian of the PSLR. To the reviewers, your adjudication lays the foundation for each edition, year-in-yearout. Your support and contribution to the PSLR remains invaluable. To Lizette Hermann, Elzet Hurter and Mornay Hassen, thank you for your continued and immeasurable support throughout this journey. To Primrose E.R Kurasha, thank you for believing in me and for guiding me. I am forever indebted to you my friend. To my family: Elizabeth Mtshweni; Jostina Mtshweni; Clayton Mtshweni; Lucas Berto Mateus; Stephine Mashilo and Lerato Mashilo, words cannot begin to express my gratitude for all the support you have given me throughout this journey. Thank you for keeping me sane through one of the toughest times of my 'publishing' career. Thank you for the endless amount of support and the unconditional love you give me always. You are the power & oil that kept this engine running, all by the sufficient grace of God. I hereby pass the baton and entrust the next Editor-in-Chief with the difficult task of running faster and running a better marathon than myself and my predecessors. To you future author, I implore you to start writing, for the water does not flow until the faucet is turned on. To you the reader, Jurgen Zwecker was right: enjoy the read - without fear to question what is in front of you, for that is the only way we, as scholars, grow. Simon Motshweni Editor-in-Chief 2020